The Interaction between Rice ERF3 and WOX11 Promotes Crown Root Development by Regulating Gene Expression Involved in Cytokinin Signaling. Issue 9 (25th August 2015) - Zhao, Yu; Cheng, Saifeng; Song, Yaling; Huang, Yulan; Zhou, Shaoli; Liu, Xiaoyun; Zhou, Dao-Xiu
Abstract : The rice AP2/ERF protein ERF3 interacts with the WUSCHEL-related homeobox protein WOX11 to regulate the cytokinin-responsive gene RR2 in development of crown roots. Abstract: Crown roots are the main components of the fibrous root system in rice ( Oryza sativa ). WOX11, a WUSCHEL -related homeobox gene specifically expressed in the emerging crown root meristem, is a key regulator in crown root development. However, the nature of WOX11 function in crown root development has remained elusive. Here, we identified a rice AP2/ERF protein, ERF3, which interacts with WOX11 and was expressed in crown root initials and during crown root growth. Functional analysis revealed that ERF3 was essential for crown root development and acts in auxin- and cytokinin-responsive gene expression. Downregulation of ERF3 in wox11 mutants produced a more severe root phenotype. Also, increased expression of ERF3 could partially complement wox11, indicating that the two genes functioned cooperatively to regulate crown root development. ERF3 and WOX11 shared a common target, the cytokinin-responsive gene RR2. The expression of ERF3 and WOX11 only partially overlapped, underlining a spatio-temporal control of RR2 expression and crown root development. Furthermore, ERF3-regulated RR2 expression was involved in crown root initiation, while the ERF3/WOX11 interaction likely repressed RR2 during crown root elongation. These results define a mechanism regulating gene expression involved in cytokinin signaling during different stages of crown root development in rice.